From Mudéjar Tolerance to Morisco Expulsion: Discourses of Heresy and the Construction of Islamic Identity in Post-Reconquista Spain. (Al-Aasar, 2025)
This study examines the historical trajectory of Muslim communities in Spain, focusing on the transition from Mudéjar tolerance to the forced assimilation and eventual expulsion of the Moriscos in post-Reconquista Spain (1492–1614). It explores how Christian authorities constructed Islam as heresy, employing legal, religious, and social mechanisms to justify coercive assimilation, including linguistic bans, cultural restrictions, inquisitorial surveillance, and collective punishment. Drawing on primary sources such as Inquisition records, royal edicts, aljamiado manuscripts, and contemporaneous writings (e.g., the Young Man of Arévalo), alongside secondary scholarship from Western and contemporary Muslim researchers, the study analyzes both state-imposed conformity and community-driven strategies for preserving Islamic faith and cultural identity. Findings highlight that Moriscos maintained clandestine religious practices, intellectual engagement, and trans-Mediterranean networks with North Africa and the Ottoman Empire, demonstrating resilience under systemic oppression. The study situates these historical experiences within broader European patterns of minority governance, revealing parallels with contemporary policies affecting Muslim communities in countries such as France, Germany, Italy, Denmark, and Switzerland. By integrating historical and contemporary perspectives, the research underscores the enduring significance of religious tolerance, minority rights, and identity preservation, offering insights into both early modern Iberian governance and current European approaches to multiculturalism and integration.